Ефективність зниження викидів оксидів азоту системою ступеневого спалювання вугілля котла ТПП-312 блоку № 6 ДТЕК Ладижинська ТЕС на основних режимах навантаження - Кобзар, С. Г.; Халатов, А. А. (НТУ "ХПІ", 2015)
Проведено дослідження ефективності зниження оксидів азоту системою ступеневого спалювання вугілля котла ТПП-312 на основних режимах навантаження та визначено вплив її експлуатації на основні технологічні параметри топки. Отримано, що для забезпечення умов рідкого шлаковидалення в низу топки мінімальне навантаження блоку не повинно бути менше 210 МВте, а витрата палива в додаткові пальники не перевищувати 10 % витрати вугілля. Для попередження шлакування системи підвісних ширм на максимальних навантаженнях існуюча система потребує додаткової модернізації. Для забезпечення максимального відновлення оксидів азоту системою ступеневого спалювання вугілля значення надлишку повітря на початку зони допалювання повинно становити 0,9.

The investigation of the efficient reduction of nitrogen oxide emissions by the phasic coal firing system for the TPP 312 boiler under basic load conditions has been carried out. The impact of its operation on the basic process parameters of the furnace has been determined. When the TPP 312 boiler operates with the phasic coal firing system at maximum loads the increase in maximum local temperature by 200 C in comparison with the standard boiler is observed. To prevent the steam superheater slagging at maximal loads the available phasic firing system must be improved. To provide safe operation of the boilers at maximum loads it is recommended to mount the additional smoke sucker to supply cold furnace gases to the upper part of the furnace and in this case the coal input in additional burners should be limited to the 10 % percent of the total fuel rate. To provide a maximum level of nitrogen oxide reduction by the phasic firing system the value of the excess air at the origin of the afterburning zone must be equal to 0.9. It has been established that to provide conditions for the liquid slag disposal at the bottom of the furnace the minimum load of the boiler set should not exceed 210 MWe and the fuel input to additional burners should not exceed 10 % of the coal input.
Efficient reduction of nitrogen oxide emissions using the phasic coal firing system of the tpp 312 boiler used by the block no6 of ladyzhinskaia power station under basic load conditions
Keywords: енергетика; технологічні параметри топки; пальники; шлаковидалення; екологічні параметри; coal burning; burner; nitrogen oxides; phasic coal firing